SKRINING BAKTERI SELULOLITIK ASAL TANAH KEBUN PISANG - meli Astriani (Biota, 2017)
Cellulose is the most abundant biomass in nature. Utilization of organic wastes can be improved by changing the cellulose from wastes into products which have the economic value with the help of cellulolytic bacteria. Cellulolytic bacteria are bacteria that have the ability to produce cellulase. Cellulase can degrade cellulose as the substrate. The aim of this study were to obtain cellulolytic bacteria, and to provide an information about the test of cellulolytic bacterial activity. Stages of this study are as follows:  isolation and purification, morphological and physiological characterization of cellulolytic bacteria, tests enzyme activity. Results showed that there were two types of cellulolitic bacteria which had been obtained, namely isolate A1 and A2 that were able to grow on CMC media and each isolate has the ability to form a clear zone of 1.3 and 1.25 mm, respectively. Isolate A1 belonged to genus Pseudomonas with enzyme activity of 1.248 unit/ml.